Internet financial reporting adoption: Exploring the influence of board role performance and isomorphic forces - Juma Bananuka; Sadress Night; Muhammed Ngoma; Grace Muganga Najjemba (Journal of Economics, Finance and Administrative Science, 2019)
This study aims to examine the contribution of board role performance and isomorphic forces on internet financial reporting. Design/methodology/approach This study is cross-sectional and correlational. Data were collected through a questionnaire survey of 40 financial services firms. The study's unit of analysis was a firm. Chief Internal Auditors and Chief Finance Officers were the study's unit of inquiry. Data were analyzed through correlation coefficients and linear regression using Statistical Package for Social Sciences. Findings The results suggest that board role performance and isomorphic forces are significant predictors of internet financial reporting. However, board role performance is not a significant predictor of internet financial reporting in the presence of isomorphic forces. The control and strategic roles of the board are positively and significantly associated with internet financial reporting unlike the service role. Only the coercive isomorphism is positively and significantly associated with internet financial reporting unlike the normative and mimetic isomorphism. Originality/value This study provides initial empirical evidence on the contribution of board role performance and isomorphic forces on internet financial reporting using evidence from Uganda's financial service firms. To the researcher's knowledge, this is the first perception-based study on internet financial reporting.
Keywords: 330; Internet ﬁ nancial reporting; Isomorphicforces